Влияние конструкционных параметров и эксплуатационных факторов на частоты колебаний крышек гидротурбин - Мисюра, С. Ю. (НТУ "ХПИ", 2014)
Представлена методика расчета собственных частот колебаний крышки гидротурбины в вакууме и при взаимодействии с водой с учетом предварительно напряженного состояния конструкции. На тестовом примере проверена работоспособность предлагаемого подхода и подтверждена достоверность результатов, полученных на его основе. Результаты, полученные по предлагаемому подходу, отличаются от экспериментальных данных от 0,5 до 11 %.

The technique for calculating the natural vibration frequencies of hydro turbine lid in vacuum, in contact with water and taking into account the pre-stressed state of the structure is presented. Functionality of the proposed approach was checked on the test case, and the accuracy of the results, obtained on its basis was confirmed. The results obtained due to the proposed approach differ from the experimental data by 0.5-11%. The difference between the results obtained based on the proposed approach and calculated by the formula is 0.9-15%. Based on the methodology, analysis of the influence of factors on the first natural vibration frequency of the hydro turbine lid structure in a vacuum and taking into account the effect of water and the pre-stressed state of the structure was performed. It was found that in this structure of the hydro turbine lid: – hydroelastic vibration frequency decreases with an increase in the water volume depth; – vibration frequency decreases with an increase in mass loads M; – vibration frequency decreases with an increase in water pressure; – consideration of the pre-stressed state has no significant effect.
Influence of structural parameters and operational factors on the vibration frequencies of hydroturbine lids
Keywords: характеристики упругих оболочек; колебания конструкций; предварительно напряженное состояние; внутреннее давление; vibrations; pre-stressed state; intrinsic pressure; hydro turbine lid